Aligning Social and Environmental Responsibility Policies Based on Creating Shared Value Concept: A Case Study at PT Petrokimia Gresik - Premananto, Gancar Candra; Prayodhia Sanwasi, Dimas (UIN Sunan Kalijaga Yogyakarta, 2023)
This study investigates how companies can achieve a balance between economic profit and social/environmental responsibility through the Creating Shared Value (CSV) approach. PT Petrokimia Gresik serves as the subject of the research, analyzing its Social and Environmental Responsibility programs within the context of CSV. The research method employed an exploratory case study with a qualitative approach. Data were obtained through in-depth interviews, Focus Group Discussions (FGD), and a review of documents related to the implementation of Social and Environmental Responsibility programs in the company. Respondents, including internal company stakeholders, participated in interviews and FGDs. The findings revealed deficiencies in the formulation of Social and Environmental Responsibility programs, hindering alignment with the CSV concept. However, six existing programs have moved toward the CSV concept by providing economic and social/environmental benefits, aligning with the company's short- and long-term strategies. These findings underscore the importance of adjusting company policies to be more integrated with CSV principles to achieve more optimal success in fulfilling social and environmental responsibilities while obtaining economic gains. Keywords: Creating Shared Value, Social and Environmental Responsibility, PT Petrokimia Gresik Studi ini menyelidiki bagaimana perusahaan dapat mencapai keseimbangan antara keuntungan ekonomi dan tanggung jawab sosial/lingkungan melalui pendekatan Creating Shared Value (CSV). PT Petrokimia Gresik menjadi subjek penelitian yang menganalisis program-program Tanggung Jawab Sosial dan Lingkungan dalam konteks CSV. Metode penelitian menggunakan studi kasus eksploratif dengan pendekatan kualitatif. Data diperoleh melalui wawancara mendalam, Focus Group Discussion (FGD), dan tinjauan dokumen terkait pelaksanaan program-program Tanggung Jawab Sosial dan Lingkungan di perusahaan. Responden, termasuk pihak internal perusahaan, terlibat dalam wawancara dan FGD. Temuan menunjukkan kekurangan dalam penyusunan program Tanggung Jawab Sosial dan Lingkungan, yang menghambat keselarasan dengan konsep CSV. Namun, enam program yang ada telah menuju konsep CSV dengan memberikan manfaat ekonomi dan sosial/lingkungan, sejalan dengan strategi jangka pendek dan panjang perusahaan. Temuan ini menegaskan pentingnya penyesuaian kebijakan perusahaan agar lebih terintegrasi dengan prinsip-prinsip CSV guna mencapai kesuksesan yang lebih optimal dalam memenuhi tanggung jawab sosial dan lingkungan sambil memperoleh keuntungan ekonomi. Kata kunci: Creating Shared Value, Tanggung Jawab Sosial dan Lingkungan, PT Petrokimia Gresik